Temporal trends and spatial patterns of Hepatitis C-related mortality in Brazil - Elodie Bomfim Hyppolito; Alberto Novaes Ramos Júnior; Anderson Fuentes Ferreira; Thor Oliveira Dantas; José Milton de Castro Lima; Taynara Laís Silva; Roberto da Justa Pires Neto (Revista de Saúde Pública)
ABSTRACT OBJECTIVE: To analyze the trends and spatial patterns of hepatitis C-related mortality in Brazil from 2000 to 2020. METHODS: A population-based, mixed ecological study of spatial and temporal trends, using secondary data from death certificate (DC) registries, in which hepatitis C was mentioned as an underlying or associated cause of mortality. Temporal trends were analyzed by joinpoint regression, and spatial analysis by the distribution of adjusted rates by age and sex, and spatial autocorrelation by the local Moran index and the Getis-Ord Gi* index (Gi star). RESULTS: From 2000 to 2020, 64,029 deaths due to hepatitis C were recorded in the Mortality Information System (SIM), representing 0.26% of deaths in Brazil. Most deaths were due to underlying causes (n = 33,652, 52.6%). Areas with high rates in all five analyzed periods were identified in the states of São Paulo, southern Minas Gerais, southern Rio de Janeiro, northern Paraná, southern and coastal Santa Catarina, eastern Mato Grosso do Sul, and Rio Grande do Sul. The states of Acre and southern Amazonas showed high rates after 2004, which spread to northern Rondônia from 2016 to 2020. The joinpoint regression model showed an increasing trend in hepatitis C mortality in Brazil from 2000 to 2015, but a decreasing trend from 2016-2020. The mortality rate was higher in men and people over sixty years of age. CONCLUSION: Differences were observed in the temporal and spatial trend of hepatitis C mortality in different regions of Brazil. These data may support the design of hepatitis C elimination strategies in Brazil, according to regional specificities.